Fibril-Forming Motifs Are Essential and Sufficient for the Fibrillization of Human Tau - Meng, Sheng-Rong; Zhu, Ying-Zhu; Guo, Tong; Liu, Xiao-Ling; Chen, Jie; Liang, Yi (PLOS ONE, 2012)
Background The misfolding of amyloidogenic proteins including human Tau protein, human prion protein, and human α-synuclein is involved in neurodegenerative diseases such as Alzheimer disease, prion disease, and Parkinson disease. Although a lot of research on such amyloidogenic proteins has been done, we do not know the determinants that drive these proteins to form fibrils and thereby induce neurodegenerative diseases. In this study, we want to know the role of fibril-forming motifs from such amyloidogenic proteins in the fibrillization of human Tau protein. Methodology/Principal Findings As evidenced by thioflavin T binding and turbidity assays, transmission electron microscopy, and circular dichroism, fibril-forming motifs are essential and sufficient for the fibrillization of microtubule-associated protein Tau: only when both of its fibril-forming motifs, PHF6 and PHF6*, are deleted can recombinant human Tau fragment Tau244–372 lose its ability to form fibrils, and the insertion of unrelated fibril-forming motifs from other amyloidogenic proteins, such as human prion protein, yeast prion protein, human α-synuclein, and human amyloid β, into the disabled Tau protein can retrieve its ability to form fibrils. Furthermore, this retrieval is independent of the insertion location on Tau244–372. Conclusions/Significance We demonstrate for the first time that insertion of fibril-forming motifs can replace PHF6/PHF6* motifs, driving human Tau protein to form fibrils with different morphologies and different kinetic parameters. Our results suggest that fibril-forming motifs play a key role in the fibrillization of human Tau protein and could be the determinants of amyloidogenic proteins tending to misfold, thereby causing the initiation and development of neurodegenerative diseases. Our study also touches on the importance of amyloid “strains”: changes to the amyloidgenic driver region results in altered structural morphologies at the macromolecular level.